THE GENERAL VIEW OF PSYCHOTHERAPY / THE META MODEL AND PREDICTIVE / PREVENTATIVE MENTAL HEALTH CARE HAVE SEVEN GROUPS OF REASONS THAT AFFECT THE FOUR CORNERSTONES OF WELL-BEING. - Heiska, Juhani (IJRDO - Journal of Social Science and Humanities Research, 2022)
A common goal among the many schools of psychotherapy these days is to find elements of psychotherapy that apply to many of them. The basis for which a general view like this can be found consists at least of the language and terms used, discovery of new activities, the structure of therapy and the work environment. Since the realization of psychotherapy also attempts to prevent a patient’s situation from worsening, the following question comes up: does the search for a psychotherapy metamodel feature elements that are similar to predictive mental health care? Mental health care in Finland employs a categorization of seven reasons and four cornerstones of well-being to prevent mental malaise, mental disorders, and negative exceptional behavior. This study collected a file of psychotherapeutic research results and compared it against a file regarding predictive mental health care, which affirmed the thesis “the general view of psychotherapy and preventative mental health care have a functional common categorization that consists of seven groups of reasons and four cornerstones”. KEYWORDS: 7x4-field, psychotherapy meta model, preventive mental work